Efektivitas Metode Hamidi Terhadap Prestasi Belajar Khat Arab Siswa Sekolah Kaligrafi Al-Qur’an (Sakal) Denanyar Jombang - Rohman Amirul Mukminin; Dian Kusuma Wardani; Waslah Waslah (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2022)
The problem behind this research is that researchers wish to examine Arabic khot using the Hamidi method, which is currently becoming a trend among the general public. Calligraphy art, which is a form of Islamic art heritage in the form of beautiful writing, is very important until now. This research uses quantitative methods by presenting data in the form of questionnaires, interviews, observation, and documentation in order to obtain research material that will guide the continuity and success of the research. With the data that had been presented, the researcher found that there was effectiveness in learning Arabic khot using the Hamidi method. From the research that has been done, there is a finding that presents the results of the analysis of the effect of the Hamidi method on student achievement of SAKAL in Denanyar Jombang.